Pembentukan wawasan global mahasiswa dalam mata kuliah Pendidikan Kewarganegaraan di FKIP Universitas Ahmad Dahlan - Aulia, Syifa Siti (Universitas Negeri Yogyakarta, 2016)
This research was aimed at answering about globalizing challenges citizen, especially young citizen. Teaching and learning in higher education including Citizenship Education is still conventional emphasizing learning process as the process of inculcating the value of smart and good citizen mainly related to the establishment of global competence of citizens. This study uses qualitative approach to explore the meaninful of practices and sciences of Citizenship Education as character education and global competencies of citizens. Practically, this research was expected to provide for practitioners and scientists of education, especially for Citizenship Education as character development courses in college, especially in the formation of global competencies of young citizens.